Trauma, Love, and Identity Development in Rowling’s Harry Potter and the Prisoner of Azkaban - You-shuan Shiong; Ya-huei Wang (Journal of Language and Literature, 2022)
Persons in the stage of adolescence are eager to know who they are. They are curious about their unique characteristics and identities and how they can start to bring about the self-realization that provides a gateway to adulthood by exploring those characteristics and identities. In this process of self-exploration, adolescents who receive encouragement as they search for an authentic identity, though they sometimes have conflicts with parents and others, are likely to develop a secure ego-identity and a strong sense of independence and self-control. By contrast, adolescents who fail to receive encouragement during the process of identity exploration, for whatever reason, may remain unsure about who they are, and hence feel insecure and confused about themselves as well as their future.  The present study uses the fictional character Harry Potter to explore these issues in greater depth, mainly focusing on his early adolescent years—that is, when he is 11-13 years old. The study demonstrates that Harry Potter can manage to resolve conflicting ideas and thereby lay the foundations for a healthy ego-identity despite difficult circumstances. The study uses Erikson’s and other psychologists’ understanding of the importance of self-exploration in adolescence as an interpretive lens to examine the dynamics of trauma, love, and self-realization in Rowling’s Harry Potter and the Prisoner of Azkaban. More specifically, it considers how family love (or the lack thereof), mentorship, and friendship in adolescence impact Harry’s mental and physical behaviors and influence the development of his identity.